Photosystem II Inspired NiFe‐Based Electrocatalysts for Efficient Water Oxidation via Second Coordination Sphere Effect - Liu, Ming; Li, Na; Wang, Xuemin; Zhao, Jia; Zhong, Di‐Chang; Li, Wei; Bu, Xian‐He (Angewandte Chemie International Edition, 2023)
The mismatched fast‐electron‐slow‐proton process in the electrocatalytic oxygen evolution reaction (OER) severely restricts the catalytic efficiency. To overcome these issues, accelerating the proton transfer and elucidating the kinetic mechanism are highly sought after. Herein, inspired by photosystem II, we develop a family of OER electrocatalysts with FeO6/NiO6 units and carboxylate anions (TA2−) in the first and second coordination sphere, respectively. Benefiting from the synergistic effect of the metal units and TA2−, the optimized catalyst delivers superior activity with a low overpotential of 270 mV at 200 mA cm−2 and excellent cycling stability over 300 h. A proton‐transfer‐promotion mechanism is proposed by in situ Raman, catalytic tests, and theoretical calculations. The TA2− (proton acceptor) can mediate proton transfer pathways by preferentially accepting protons, which optimizes the O−H adsorption/activation process and reduces the kinetic barrier for O−O bond formation. We developed an electrocatalytic model that is designed to obtain superior oxygen evolution reaction activity (270 mV at 200 mA cm−2) and cycle stability (over 300 h) by tuning the proton transfer pathway. The electron‐rich terephthalic acid anion located in the second coordination sphere of the active center can mediate proton transfer pathways by preferentially accepting protons, which reduces the kinetic barrier for O−O bond formation.